(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The basic purpose of this study was to evaluate the strategic planning practices by Financial Sectors and how owners and managers of these Financial Sectors play their roles in it in Tanzania. The other study objective was to ascertain if differences in strategic planning practices existed with respect to Strategic Planning in Tanzania’s Financial Sectors. The study discovered the main scopes of strategic planning are environmental scanning, mission and vision, implementation incentives, time horizon of strategic planning, evaluation and control, employee involvement in strategic planning, the structure of strategic planning as well as source of information concerning the environment. Consequently the study discovered that vision and mission, a formality of strategic planning and evaluation and control were the most valued factors. The study concluded that there is insignificant statistical difference among managers and owners in their positions during strategic planning process. The study offers various dimensions of strategic planning that Financial Sectors of Tanzania can implement to be competitive and sustainable.